Enhanced cellulase production by Penicillium oxalicum for bio-ethanol application. (July 2015) - Saini, Reetu; Saini, Jitendra Kumar; Adsul, Mukund; Patel, Anil Kumar; Mathur, Anshu; Tuli, Deepak; Singhania, Reeta Rani
Highlights: A potent cellulolytic fungal strain was isolated and identified as P. oxalicum. Media engineering enhanced cellulase production by 1.7-fold. In bioreactor incubation time was reduced for producing same cellulase titer. In-house cellulase showed equal hydrolysis potential as that of commercial ones. Abstract: Present study was focused on cellulase production from an indigenously isolated filamentous fungal strain, identified as Penicillium oxalicum . Initially, cellulase production under submerged fermentation in shake flasks resulted in cellulase activity of 0.7 FPU/mL. Optimization of process parameters enhanced cellulase production by 1.7-fold and resulted in maximum cellulase activity of 1.2 FPU/mL in 8 days. Cellulase production was successfully scaled-up to 7 L fermenter under controlled conditions and incubation time was reduced from 8 days to 4 days for achieving similar cellulase titer. Optimum pH and temperature for activity of the crude enzyme were pH 5 and 50 °C, respectively. At 50 °C the produced cellulase retained approximately 50% and 26% of its activity at 48 h and 72 h, respectively. Hydrolytic efficiency of P. oxalicum was comparable to commercial cellulase preparations which indicate its great potential for application in the lignocellulose hydrolysis.